Using Scientific Publications to Evaluate Government R&D Spending: The Case of Energy - David Popp (Center for Economic Studies and ifo Institute (CESifo), 2015)
The mix of public and private research funding investments in alternative energy presents a challenge for isolating the effect of government R&D funding. Factors such as energy prices and environmental policy influence both private and public R&D decisions. Moreover, because government R&D is further upstream from the final commercialized product, it may take several years for its effect on technology to be realized. Combining data on scientific publications for alternative energy technologies with data on government R&D support for these technologies, we address these challenges. First, we ask how long it takes for energy R&D to provide successful research outcomes. We both provide information on the lags between research funding and new publication and link these articles to citations in U.S. energy patents. One million dollars in additional government R&D funding leads to 1-2 additional publications, but with lags as long as ten years between initial funding and publication. Second, we ask whether adjustment costs associated with large increases in research funding result in diminishing returns to government R&D. There is no evidence of diminishing returns on the level of publication output, but some evidence that additional funding leads to lower quality publications, using citations as a measure of publication quality.
Keywords: O38; Q42; Q48; Q55; 330; public R&D; publication data; solar energy; wind energy; biofuels; energy efficiency